Changes of brain resting state functional connectivity predict the persistence of cognitive rehabilitation effects in patients with multiple sclerosis. (May 2014) - Parisi, Laura; Rocca, Maria A; Mattioli, Flavia; Copetti, Massimiliano; Capra, Ruggero; Valsasina, Paola; Stampatori, Chiara; Filippi, Massimo
Objective: We investigated whether the efficacy of 12-week cognitive rehabilitation in MS patients persists six months after treatment termination and, together with resting state (RS) functional connectivity (FC), changes on neuropsychological performance at follow-up. Methods: Eighteen MS patients with cognitive deficits, assigned randomly either to undergo treatment ( n =9) or not ( n =9), underwent neuropsychological evaluation at baseline (t0), after 12 weeks of rehabilitation (t1) and at six-month follow-up (t2). RS fMRI was obtained at t0 and t1. Changes in neuropsychological performance and their correlations with RS FC modifications were assessed using longitudinal linear models. Results: At t2 vs. t0, compared with the control group, treated group patients improved in tests of attention, executive function, depression and quality of life (QoL). Neuropsychological scores in these tests at t2 were significantly correlated with RS FC changes in cognitive-related networks and RS FC of the anterior cingulum. RS FC changes in the default mode network predicted cognitive performance and less severe depression, whereas RS FC changes of the executive network predicted better QoL. Discussion: Changes in RS FC of cognitive-related networks helps to explain the persistence of the effects of cognitive rehabilitation after several months in relapsing–remitting multiple sclerosis patients and their improvement on depression and QoL scales.